RNA methylation in plants: An overview - Shinde, Harshraj; Dudhate, Ambika; Kadam, Ulhas S.; Hong, Jong Chan (Frontiers in Plant Science, 2023)
RNA methylation is a key post-transcriptional modification affecting gene regulation. In plants, over 200 different types of RNA modifications are identified. The mystery of RNA methylation has been revealed in animals, and its biological role and applications have become progressively apparent. However, RNA methylation is relatively less understood in plants. Recently, RNA methylation has advanced rapidly in plant science research, and it has become apparent that RNA methylation plays a critical role in plant development. This review summarizes existing knowledge about the methylation of RNA in plant development. We emphasize the writers, erasers, and readers of plants, the occurrence, methods, and software development in RNA methylation. N6-methyladenosine (m6A) methylation is the most common and abundant RNA methylation in plants. In Arabidopsis, the mutation in writers, erasers, and readers of RNA methylation has impacted the phenotype of the plant. The importance of RNA methylation in RNA mobility has also been proven, where methylated TRANSLATIONALLY CONTROLLED TUMOR PROTEIN 1-messenger RNA moves from shoot to root, and unmethylated TCTP1-mRNA doesn’t. Methylated RNA immunoprecipitation coupled with next-generation sequencing has been a milestone in plant RNA methylation analysis. This method has been successfully applied in plants like rice, Arabidopsis, Brassica, maize, etc., to study transcriptome-wide RNA methylation. Various software or tools have been used to detect methylated RNAs at the whole transcriptome level; most are model-based analysis tools (for example, MACS2). Finally, the limitations and future prospects of methylation RNA research have been documented.